A simple dynamic integrated provisioning - Ye, Yinghua (IEEE Communications magazine)
This article presents a simple integrated provisioning/protection scheme to dynamically allocate restorable bandwidth guaranteed paths in IP over WDM networks. A guaranteed restorable path implies that a flow of data is successfully routed if both an active path and another alternate link-disjoint path are found at the same time. Unlike the conventional approach, where the IP and WDM layers are not aware of each other, the new scheme takes advantage of the development in generalized multi-protocol label switching (GMPLS) to provide integrated end-to-end survivability by incorporating network state information from both layers (e.g., the cost information in physical links, the bandwidth usage on each lightpath, and intermediate router speed) into protection path allocation. Simulation results are used to evaluate the performance of the new scheme and show that the proposed protection approach can efficiently improve the network utilization, and deliver reliable services